2016
DOI: 10.1016/j.chemgeo.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium–hafnium and rare earth element signatures discriminating the effect of atmospheric fallout from hydrothermal input in volcanic lake water

Abstract: , L. Brusca, et al.. Zirconiumhafnium and rare earth element signatures discriminating the effect of atmospheric fallout from hydrothermal input in volcanic lake water. Chemical Geology, Elsevier, 2016Elsevier, , 433, pp.1-11. <10.1016Elsevier, /j.chemgeo.2016.04.002>. A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT1 Zirconium-hafnium and rare earth element signatures discriminating the effect of atmospheric fallout from hydrothermal input in volcanic lake water (HREE) enrichments in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 48 publications
(70 reference statements)
2
14
0
Order By: Relevance
“…As mentioned above, HREE enrichment has been commonly reported in water with high carbonate and CO 2 concentrations. It is interesting that CO 2 -rich waters (pH=9) from the top and bottom of ‗Specchio di Venere' Lake also enrich in MREE (Inguaggiato et al, 2016). The REE pattern of lake water was similar to a desert varnish of Saharan origin, cosisting mainly Fe-and Mn-oxyhydroxide coatings and clay minerals.…”
Section: Shale-normalized Ree Patterns In Rainwatermentioning
confidence: 92%
See 3 more Smart Citations
“…As mentioned above, HREE enrichment has been commonly reported in water with high carbonate and CO 2 concentrations. It is interesting that CO 2 -rich waters (pH=9) from the top and bottom of ‗Specchio di Venere' Lake also enrich in MREE (Inguaggiato et al, 2016). The REE pattern of lake water was similar to a desert varnish of Saharan origin, cosisting mainly Fe-and Mn-oxyhydroxide coatings and clay minerals.…”
Section: Shale-normalized Ree Patterns In Rainwatermentioning
confidence: 92%
“…Aubert et al (2002) found that rainwater and snow from east France showed HREE enrichment similar to seawater. This shale-normalized pattern was commonly detected in natural waters with high carbonate or CO 2 concentration (Johannesson and Lyons, 1994;Choi et al, 2009;Inguaggiato et al, 2016). The enrichment in HREE is the result of the formation of stable carbonate complexes in water where HREE preferentially form stronger carbonate complexes than MREE and LREE (Elerfield, 1988;.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…This coherence is absent during aqueous processes due to the different grades of Zr and Hf hydrolysis and dissolved complexation in natural waters (Aja et al, 1995;Veyland et al, 1998;Byrne, 2002;Hagfeldt et al, 2004;Messner et al, 2011a;2011b;Inguaggiato et al, 2015Inguaggiato et al, , 2016Censi et al, 2017). Aqueous environments usually make Hf more surface-reactive than Zr, which changes the associated Zr/Hf with respect to the range of values recognised in rocks and minerals and provides a useful signature of solid-liquid processes.…”
Section: Introductionmentioning
confidence: 99%